2011
DOI: 10.1186/1477-5956-9-40
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of saccharopolyspora spinosa SP06081 and PR2 strains reveals the differentially expressed proteins correlated with the increase of spinosad yield

Abstract: BackgroundSaccharopolyspora spinosa produces the environment-friendly biopesticide spinosad, a mixture of two polyketide-derived macrolide active ingredients called spinosyns A and D. Therefore considerable interest is in the improvement of spinosad production because of its low yield in wild-type S. spinosa. Recently, a spinosad-hyperproducing PR2 strain with stable heredity was obtained from protoplast regeneration of the wild-type S. spinosa SP06081 strain. A comparative proteomic analysis was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…The positive correlation between the potency against hypoxia and spinosad production was also observed during the traditional genetic improvement of the SP06081 strain. Moreover, differential proteomic analysis of S. spinosa SP06081 and the spinosad-hyperproducing PR2 strain, which was obtained from its protoplast regeneration, demonstrated that a group of proteins involved in anti-oxidant stress was significantly up-regulated in the PR2 strain [37]. For the aforementioned reasons, further investigations on the improvement of oxygen uptake properties of the SP06081 strain were conducted to promote spinosad biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between the potency against hypoxia and spinosad production was also observed during the traditional genetic improvement of the SP06081 strain. Moreover, differential proteomic analysis of S. spinosa SP06081 and the spinosad-hyperproducing PR2 strain, which was obtained from its protoplast regeneration, demonstrated that a group of proteins involved in anti-oxidant stress was significantly up-regulated in the PR2 strain [37]. For the aforementioned reasons, further investigations on the improvement of oxygen uptake properties of the SP06081 strain were conducted to promote spinosad biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The first comprehensive and comparative proteomic analysis of Sa. spinosa strains using label‐free methods was presented by Luo et al in 2011. Twelve proteins directly related to spinosad biosynthesis were identified from the wild‐type Sa.…”
Section: Strategies For Spinosad Overproduction In Sa Spinosamentioning
confidence: 99%
“…These results provided clues that these differentially expressed proteins may contribute to the improvement of spinosad production. The Luo et al study indicated that proteomics can provide information for understanding the molecular and metabolic mechanisms that may lead to the improvement of spinosad production; furthermore, it can be used to provide information about the regulatory network in Sa. spinosa .…”
Section: Strategies For Spinosad Overproduction In Sa Spinosamentioning
confidence: 99%
“…Although a great number of attempts have been made for metabolic engineering of spinosad biosynthesis, there are only a few reports concerning the regulation of the expression of the spinosad gene cluster (31)(32)(33). In fact, there is as yet no report of yield improvement through manipulation of regulatory genes.…”
Section: Discussionmentioning
confidence: 99%